2019
DOI: 10.1037/amp0000557
|View full text |Cite
|
Sign up to set email alerts
|

Queering the history of South African psychology: From apartheid to LGBTI+ affirmative practices.

Abstract: This article constructs a brief history of how lesbian, gay, bisexual, transgender and intersex (LGBTI) issues have intersected with South African psychology at key sociopolitical moments, filling a gap in current histories. Organized psychology-a primary focus of this analysis-since its first formations in 1948, mostly colluded with apartheid governments by othering queerness as psychopathology or social deviance. The National Party, both homophobic and racist, ruled the country from 1948 until the first demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…18 Our scholar activism has, therefore, aspired to leverage progressive platforms to actively destabilise these epistemic injustices. 19,20 In 2013, their position statement on sexual and gender diversity centred the national Psychological Society of South Africa (PsySSA) as an affirmative body that will not tolerate homophobia, biphobia, or transphobia in the profession. 21 An affirmative stance is an ethical practice that includes respectful recognition of diversity among people, and critical, contextual awareness about the struggles and strengths that inform the lived experiences of LGBT+ people.…”
Section: Disrupting Hetero-cis-normativitymentioning
confidence: 99%
See 1 more Smart Citation
“…18 Our scholar activism has, therefore, aspired to leverage progressive platforms to actively destabilise these epistemic injustices. 19,20 In 2013, their position statement on sexual and gender diversity centred the national Psychological Society of South Africa (PsySSA) as an affirmative body that will not tolerate homophobia, biphobia, or transphobia in the profession. 21 An affirmative stance is an ethical practice that includes respectful recognition of diversity among people, and critical, contextual awareness about the struggles and strengths that inform the lived experiences of LGBT+ people.…”
Section: Disrupting Hetero-cis-normativitymentioning
confidence: 99%
“…24 Importantly, the guidelines were co-opted, as interdisciplinary resources for primary health-care interventions, by two other African countries who also participated in the early phases of its development. 20 These position statements and guidelines became more than mere knowledge outputs; they actively destabilised existing orthodoxies in health care and served as key reference points for broader epistemic disruption.…”
Section: Disrupting Hetero-cis-normativitymentioning
confidence: 99%
“…have taken steps to censure a psychologist who misrepresented psychological science in the case of Elena Klimova, who was charged under the Propaganda Ban as the host of the Deti-404 site, an online information and community site for LGBT youth . Although there are many notable exceptions, for example, professional psychology's involvement in hate speech and hate crimes in South Africa (Judge & Nel, 2018;Nel, 2014;Pillay et al, 2019), national psychology associations have not typically been engaged in LGBTQ advocacy .…”
Section: The Risks Of Action the Consequences Of Inactionmentioning
confidence: 99%
“…More than 100 psychologists in Russia, where professional psychology’s role in advocacy has not been fostered, published a blistering statement about the prosecutor’s biased expert analysis in the case of the punk rock band Pussy Riot (Radio Free Europe, 2012), and both the Russian Psychological Society and a psychological institute of higher education have taken steps to censure a psychologist who misrepresented psychological science in the case of Elena Klimova, who was charged under the Propaganda Ban as the host of the Deti-404 site, an online information and community site for LGBT youth (Horne et al, 2019). Although there are many notable exceptions, for example, professional psychology’s involvement in hate speech and hate crimes in South Africa (Judge & Nel, 2018; Nel, 2014; Pillay et al, 2019), national psychology associations have not typically been engaged in LGBTQ advocacy (Horne et al, 2019).…”
Section: Virtue Is Not Solitary: It Is Bound To Have Neighborsmentioning
confidence: 99%
“…Would this shift in the research have been facilitated had such structures and analysis existed in the United Kingdom? Consider also how Pillay et al (2019) showed there was little recognition of sexual diversity in the critical psychology of the Apartheid era in South Africa.…”
Section: Alexandra Rutherfordmentioning
confidence: 99%